2015
DOI: 10.5089/9781498315005.001
|View full text |Cite
|
Sign up to set email alerts
|

Women Workers in India: Why So Few Among So Many?

Abstract: This paper examines the determinants of female labor force participation in India, against the backdrop of India having one of the lowest participation rates for women among peer countries. Using extensive Indian household survey data, we model the labor force participation choices of women, conditional on demographic characteristics and education, as well as looking at the influence of state-level labor market flexibility and other state policies. Our main finding is that a number of policy initiatives can he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 14 publications
1
48
0
Order By: Relevance
“…The Pew Research surveys find that 84 percent of Indians agree with the statement: "when jobs are scarce, men should have more right to a job than women" (Pew Research Center 2010). Such attitudes are found to be negatively correlated with women's labor force participation across many countries and are a reflection of social norms that reinforce the traditional role of women and also mediate the way institutions treat women and perpetuate gender inequality in the labor market (Das et al 2015;World Bank 2013). Norms are often selfperpetuating, in that employers and investors look for what they expect to find.…”
Section: Discussionmentioning
confidence: 99%
“…The Pew Research surveys find that 84 percent of Indians agree with the statement: "when jobs are scarce, men should have more right to a job than women" (Pew Research Center 2010). Such attitudes are found to be negatively correlated with women's labor force participation across many countries and are a reflection of social norms that reinforce the traditional role of women and also mediate the way institutions treat women and perpetuate gender inequality in the labor market (Das et al 2015;World Bank 2013). Norms are often selfperpetuating, in that employers and investors look for what they expect to find.…”
Section: Discussionmentioning
confidence: 99%
“…Gender empowerment, identified as one of the key Sustainable Development Goals (SDGs) of the United Nations, is given major emphasis globally. The studies by several researchers across different crops, agriculture commodities, and farming systems in India (Das et al 2015;Chayal et al 2013;Waris and Viraktamath 2013) have identified the importance of gender empowerment in agriculture and found that a large gender gap in agriculture exists in India.…”
Section: Introductionmentioning
confidence: 99%
“…Female labor force participation (FLFP), which is at one-third of male labor force participation, has been falling over time. Lack of employment opportunities in the formal (organized) sector is an important contributor to the declining trend in female labor force participation (Khera, , 2016aDas et al, 2015; Chatterjee et al, 2015). Informal (unorganized) sector employment constitutes more than 90 percent of total employment, and females are largely employed in low productivity informal jobs in the agriculture and services sector.…”
Section: Introductionmentioning
confidence: 99%